Sexuality and Gender Diversity in the Liberal Catholic Discourse in Poland in the Pastoral Perspective - Laddach, Agnieszka (Open theology, 2021)
One of the most important questions in the Roman Catholic Church is the question of sexual and gender diversity. Therefore, the article presents the results of qualitative and quantitative content analysis of the Catholic sociocultural periodical Więź (Bond) from 2007 to 2020, which is the leading forum for liberal Catholic debates in Poland. The goal was to analyze the period’s narration toward current Church’s instructions on sexuality and gender diversity. Five dominant postulates were identified in Więź : (1) a discussion about people with the need to revise their or the Church’s narration on and experience of sex and gender; (2) a reevaluation of the significance and consequence of sexual revolution in Poland; (3) an organization of the understanding of body, sex, sexuality, and gender; (4) a promotion of the idea of encounter; and (5) a settlement of cases of sexual abuse in the Church. The article concludes that the presence of social dialogue on sexuality and gender diversity in the current pastoral approach of the Church in Poland requires a suspension of moral judgment and an openness from Church with a strong traditional, and rigid viewpoint to better understand the difficult spiritual and social situation of people who live contrary to the moral teachings of the Church or whose views go against these teachings.